Early Study on Embryogenesis O.woworae at Different Salinities - Fani Savitri Agatha; Mustahal Mustahal; Mas Bayu Syamsunarno; Muh. Herjayanto (Jurnal Biologi Tropis, 2021)
Oryzias woworae is an endemic fish of Sulawesi. This endemic fish naturally had faced endangered illegal and unlawful capture, therefore it is needed to be protected and conserved by a cultivation system. This research aims to provide basic information related to the cultivation of O. woworae to know the optimum salinity of hatching media and its influence on the hatchability of eggs and the length of time hatching O. woworae. This research was conducted using experimental methods and presented descriptively. The treatment used in this study is 0 ppt, 2-4 pt, 6-8 ppt, 10-12 ppt. The results showed that O. woworae eggs can hatch in salinity 0 ppt until 10-12 ppt and the best salinity for the length of hatching time is treatment of 2-4 ppt which is 7th day 14 hours 20 minutes. Treatment 0 ppt, 2-4 ppt and 6-8 ppt can reach 100%. This can be concluded that the optimum salinity of the hatching rate of Oryzias woworae until 6-8 ppt, but in treatment 10-12 ppt hatchability only gets 80% as some embryos become shrinking. Hatchability per day shows the treatment of 2-4 ppt is the best treatment, on the 7th day as much as 40% and on the 8th day as much as 40%. The optimal salinity for hatching O. woworae eggs is ÃÂ 2-4 ppt treatment, salinity that can expedite the length of hatching time and produce ÃÂ hatching rate by 100%.ÃÂ ÃÂ